Coming - Nancy, Jean-Luc 1940-2021; Van Reeth, Adèle 1982- (Fordham University Press, 2017)
Coming is a lyrical, erudite examination of the French notion of jouissance. How did jouissance evolve from referring to the pleasure of possessing a material thing (property, wealth) to the pleasure of orgasm, from appropriation to dis-appropriation, from consumption to consummation? The philosophers Adèle van Reeth and Jean-Luc Nancy engage in a lively dialogue, ranging from consumerism to video games to mysticism and from Spinoza, Hegel, andAugustine to the Marquis de Sade, Marguerite Duras, and Henry Miller. Four additional essays are new to the American edition
Keywords: Jean-Luc Nancy; Spinoza; St. Augustine; jouissance; pleasure; sexuality; SOCIAL SCIENCE / Gender Studies; Pleasure principle (Psychology); Pleasure; Psychoanalysis